2022
DOI: 10.1038/s41377-022-00932-3
|View full text |Cite
|
Sign up to set email alerts
|

Less is more: dimensionality reduction as a general strategy for more precise luminescence thermometry

Abstract: Thermal resolution (also referred to as temperature uncertainty) establishes the minimum discernible temperature change sensed by luminescent thermometers and is a key figure of merit to rank them. Much has been done to minimize its value via probe optimization and correction of readout artifacts, but little effort was put into a better exploitation of calibration datasets. In this context, this work aims at providing a new perspective on the definition of luminescence-based thermometric parameters using dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 45 publications
0
48
0
Order By: Relevance
“…Among which. lifetime-based nanothermometry, machine-learning-driven data analysis, , and more sophisticated excitation–emission schemes have the potential to make luminescence nanothermometry a routinely used practical tool in fundamental biomedical research.…”
Section: Near-infrared Luminescence For Biomedical Applicationsmentioning
confidence: 99%
“…Among which. lifetime-based nanothermometry, machine-learning-driven data analysis, , and more sophisticated excitation–emission schemes have the potential to make luminescence nanothermometry a routinely used practical tool in fundamental biomedical research.…”
Section: Near-infrared Luminescence For Biomedical Applicationsmentioning
confidence: 99%
“…This semi-invasive method offers reliable, precise, fast, and single-point or 2D thermal imaging in a wide temperature range, which can range from cryogenic temperatures to approximately 1700 °C [ 6 ]. It can be applied to macroscopic and microscopic systems, large surfaces, in vivo [ 7 , 8 ], fiber-optic probes [ 9 , 10 , 11 ], corrosive, radioactive environments [ 12 ], or high electromagnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that the use of a combination of distinct thermometric parameters could improve the reliability of thermometers [ 28 , 29 , 30 , 31 , 32 ]. In addition to reliability, this multiparametric approach could significantly improve the relative thermal sensitivity and temperature resolution of the sensor using a multiple linear regression-based strategy proposed by Carlos et al [ 33 , 34 ]. Another strategy to use several temperature-dependent luminescence parameters for the enhancement of thermometric characteristics has been reported by Khodasevich et al [ 35 ].…”
Section: Introductionmentioning
confidence: 99%